Accelerating magnetic resonance fingerprinting (MRF) using t‐blipped simultaneous multislice (SMS) acquisition. Issue 5 (8th June 2015) - Ye, Huihui; Ma, Dan; Jiang, Yun; Cauley, Stephen F.; Du, Yiping; Wald, Lawrence L.; Griswold, Mark A.; Setsompop, Kawin
Abstract : Purpose: We incorporate simultaneous multislice (SMS) acquisition into MR fingerprinting (MRF) to accelerate the MRF acquisition. Methods: The t‐Blipped SMS‐MRF method is achieved by adding a Gz blip before each data acquisition window and balancing it with a Gz blip of opposing polarity at the end of each TR. Thus the signal from different simultaneously excited slices are encoded with different phases without disturbing the signal evolution. Furthermore, by varying the Gz blip area and/or polarity as a function of repetition time, the slices' differential phase can also be made to vary as a function of time. For reconstruction of t‐Blipped SMS‐MRF data, we demonstrate a combined slice‐direction SENSE and modified dictionary matching method. Results: In Monte Carlo simulation, the parameter mapping from multiband factor (MB) = 2 t‐Blipped SMS‐MRF shows good accuracy and precision when compared with results from reference conventional MRF data with concordance correlation coefficients (CCC) of 0.96 for T1 estimates and 0.90 for T2 estimates. For in vivo experiments, T1 and T2 maps from MB=2 t‐Blipped SMS‐MRF have a high agreement with ones from conventional MRF. Conclusion: The MB=2 t‐Blipped SMS‐MRF acquisition/reconstruction method has been demonstrated and validated to provide more rapid parameter mapping in the MRF framework. Magn Reson Med 75:2078–2085, 2016. © 2015 Wiley Periodicals, Inc.